Fluorogenic ATP Analogues for Online Monitoring of ATP Consumption: Observing Ubiquitin Activation in Real Time1. Issue 45 (17th September 2013) - Hacker, Stephan M.; Pagliarini, Dana; Tischer, Thomas; Hardt, Norman; Schneider, Daniel; Mex, Martin; Mayer, Thomas U.; Scheffner, Martin; Marx, Andreas
<x xml:space="preserve">Abstract</x> Many enzymes use ATP in signal‐transducing processes or as an energy source. New fluorogenic ATP analogues signal ATP consumption by ubiquitin‐like protein‐activating enzymes in real time. Thus the inhibition and stimulation of these ATP‐processing enzymes can be studied without auxiliary enzymes and reagents. β‐Lapachone was identified as an inhibitor of the ubiquitin‐activating enzyme UBA1 (see scheme; A=acceptor, D=donor).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>